Production of nitride containing charge upon oxidation of powder-aluminum in air; Steklo i Keramika; № 3 - Ilyin A. P. Aleksandr Petrovich; An V. V. Vladimir Vilorievich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Yablunovskii G. V. (1998, 1998)
The composition of powdered aluminum mixtures oxidation products is investigated. It is shown that the final products including AlN (50%) can be used as the main charge component for nitride containing ceramics production